THE INFLUENCE OF LEVERAGE AND DIVERSIFICATION TO FINANCIAL PERFORMANCE OF GENERAL INSURANCE COMPANIESN IN INDONESIA 2010-2014 - Yulianti ,; Muhammad Nuryatno (Media Riset Akuntansi, Auditing & Informasi, 2015)
The purpose of this research is to find out the influence of leverage and diversification to financial performance of general insurance companies in Indonesia. This research uses secondary data from Indonesian general insurance companies’s financial report  within  year 2010 to 2014.The population of this research  is general insurance companies in Indonesia which listed as member of The General Insurance assosiation of Indonesia. The number of samples that used in this research are 10 general insurance companies which were selected based on purposive sampling method.This research used pooled regression models and hypothesis testing for each independent variable on dependent.The Result of this research shows that leverage and diversification significantly affect positively to general insurance company’s financial performance in Indonesia.Keywords : leverage, diversification, financial performance, insurance companies, and ROE.